(untitled) (Journal of Medical & Health Sciences Review, 2025)
The study highlights that local plant biodiversity in Tehsil Rawalakot is under serious threat due to human activities such as soil erosion, overgrazing, deforestation, and overuse of medicinal plants, with 19 species found in grave danger. Ethnomedicinal data recorded 200 plant species from 75 families, mainly documented by elderly respondents, where women held more knowledge than men. Informant consensus showed high agreement for diseases like fever, cancer, skin disorders, and pneumonia, while the lowest agreement was for ear, eye, and blood-related issues. Direct Matrix Ranking revealed Melia azedarach as the most multipurpose species, reflecting heavy community dependence on local trees. Priority Ranking indicated major threats including forest fires, construction, deforestation, and illegal timber trade. Several species such as Pinus wallichiana, Prunella vulgaris, and Dodonaea viscosa showed high use values and cultural significance. Fidelity Levels identified Berberis lyceum as the most trusted medicinal plant, while conservation assessment found 94 species vulnerable and 68 rare. The region’s biocultural diversity index was low compared to national values, and climate factors like temperature and rainfall were found to influence species distribution. Among 100 respondents, most belonged to the agriculture sector, followed by grazers, workers, others, and government employees.